TURKIC BOOK-PRINTING TERMINOLOGY: FORMATION AND DEVELOPMENT - Jurayevich, Yuldashev Ibragim (International Journal of Psychosocial Rehabilitation, 2020)
this article considers the solution of issues connected with disputable cases regarding more than 20 thousand manuscripts kept in our libraries beginning from the most ancient stone-engraving scribes up to the present time, about ten thousand of which covers in themselves information on our incomparable spiritual wealth composed of history, literature, art, politics, ethics, philosophy, medicine, mathematics, physics, chemistry, astronomy, architecture, farming, on disputable cases on etymology of some terms, their development periods, on defining the sources of their enrichment as well as regulating the terminology in these spheres.